If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -6x = 23 Solving -7 + -6x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -6x = 23 + 7 Combine like terms: -7 + 7 = 0 0 + -6x = 23 + 7 -6x = 23 + 7 Combine like terms: 23 + 7 = 30 -6x = 30 Divide each side by '-6'. x = -5 Simplifying x = -5
| 2/(x-7)=1/x | | 3y-6=5y+15-21 | | a^2+31=607 | | -5=3x+4+6x | | f^2+64=353 | | w^2+97=113 | | 5+3-2m+3(6+3m)=7m+3(5m-2) | | x+x+5=39 | | -7+5=-11x+17 | | 6x^2+11=49 | | 17x=100 | | -10x+-30=-8x | | 6x+4y+7z-4x+5z-8y= | | 150=2x^3+x^2+x+10 | | H=15t | | B=1.0 | | y-.666666667=5 | | 4(v-9)=-6v+34 | | 2x+7*-1=5 | | -31x-4x=-5-5+25x | | -10x=-8x-8 | | 28x^3+48x^7= | | (x-1)/2/5/4 | | 4n-6+4n=2 | | 9x^4-24x^3-26x^2+56x-15=0 | | 4x^2-11=26 | | f(x)=9x^4-24x^3-26x^2+56x-15 | | 49v-90=-6v+34 | | -5-8=5x+9x-21x | | 192=3X | | -8x^2=-64 | | (1-4x)(1-3x)=6x(2x-1) |